An Exact Analysis of Heat and Mass Transfer Past a Vertical Plate with Newtonian Heating - Abid Hussanan; Ilyas Khan; Sharidan Shafie (Journal of Applied Mathematics)
An exact analysis of heat and mass transfer past an oscillating vertical plate with Newtonian heating is presented. Equations are modelled and solved for velocity, temperature, and concentration using Laplace transforms. The obtained solutions satisfy governing equations and conditions. Expressions of skin friction, Nusselt number, and Sherwood number are obtained and presented in tabular forms. The results show that increasing the Newtonian heating parameter leads to increase velocity and temperature distributions whereas skin friction decreases and rate of heat transfer increases.